Qualidade do leite de cabras alimentadas com palma forrageira de variedades resistentes a cochonilha do carmim - Oliveira, Beatriz Dantas (2014)
The objective study was to evaluate the production and quality of milk goats fed different varieties of cactus resistant cochineal carmine. We used 12 lactating goats with 51.35 kg + 3.75 live weight, in three simultaneous Latin square, made up of 4 periods. The experimental treatments were: control diet ( Tifton hay and concentrate) and diets , adding to this three varieties of cactus pear ( Elephant Ear , Tiny and Bahia ) . The physico - chemical analysis ( protein, fat , lactose , acidity, total solids and solids not fat ) and sensory were performed at the Laboratory of Food Science , Department of Nutrition UFPB . There was no difference ( P > 0.05 ) between treatments for milk yield , protein and acidity, or to the attributes characteristic odor , rancid flavor and overall assessment . A reduction in lipid content in milk with use of the variety elephant ear compared to the control diet . For the characteristic flavor and characteristics after test ( intensity and persistence ) diets containing palm elephant ear and girl showed higher values than the control diet . The different varieties of palm can be fed to goats without affecting milk production and physico- chemical characteristics , not influencing the global acceptance , the use of any of these varieties for lactating goats being recommended .